Al2O3 Thin Films Prepared by a Combined Thermal‐Plasma Atomic Layer Deposition Process at Low Temperature for Encapsulation Applications. Issue 8 (30th September 2019) - Zhu, Zhen; Merdes, Saoussen; Ylivaara, Oili M. E.; Mizohata, Kenichiro; Heikkilä, Mikko J.; Savin, Hele
Abstract : In this article, a combined H2 O thermal atomic layer deposition of Al2 O3 with in situ N2 plasma treatment process at 90 °C for encapsulation applications is reported. The effect of process parameters on the growth behavior and properties of Al2 O3 thin films, such as elemental composition, residual stress, moisture permeation barrier ability, density, and roughness, is investigated. Optimization of plasma exposure time gives films with a low impurity (≈3.8 at% for hydrogen, ≈0.17 at% for carbon, and ≈0.51 at% for nitrogen), a high mass density (≈3.1 g cm −3 ), and a low tensile residual stress (≈160 MPa). A water vapor transmission rate of 2.9 × 10 −3  g m −2  day −1 is obtained for polyethylene naphthalate substrates coated with 4‐nm‐thick Al2 O3 films. Abstract : The combined H2 O thermal atomic layer deposition (ALD) with in situ N2 plasma treatment process of Al2 O3 thin films is studied. Al2 O3 films (4‐nm thick) show a good water vapor transmission rate of 2.9 × 10 −3  gm −2  day −1 . Compared with the earlier reported O2 ‐based plasma‐enhanced ALD, this combined process is likely gentler and therefore more suitable for sensitive substrates.